2016
DOI: 10.2147/amep.s94550
|View full text |Cite
|
Sign up to set email alerts
|

Improving medical graduates' training in palliative care: advancing education and practice

Abstract: The needs of an aging population and advancements in the treatment of both chronic and life-threatening diseases have resulted in increased demand for quality palliative care. The doctors of the future will need to be well prepared to provide expert symptom management and address the holistic needs (physical, psychosocial, and spiritual) of patients dealing with serious illness and the end of life. Such preparation begins with general medical education. It has been recommended that teaching and clinical experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 45 publications
4
55
0
4
Order By: Relevance
“…Over the past decade, palliative care education has been systematically integrated into medical education and has become a standardized competency for medical training . Simulation‐based medical education with standardized patients has emerged as a promising modality to teach key palliative care skills and close the education gap .…”
Section: Current Trends In Supportive Carementioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, palliative care education has been systematically integrated into medical education and has become a standardized competency for medical training . Simulation‐based medical education with standardized patients has emerged as a promising modality to teach key palliative care skills and close the education gap .…”
Section: Current Trends In Supportive Carementioning
confidence: 99%
“…Over the past decade, palliative care education has been systematically integrated into medical education and has become a standardized competency for medical training. 10 Simulation-based medical education with standardized patients has emerged as a promising modality to teach key palliative care skills and close the education gap. 11,12 In the VOICE trial (Values and Options in Cancer Care), patient-centered communication about advanced cancer diagnosis, treatment options, prognosis, and QoL was enhanced with individualized training for both the clinician and the patient.…”
Section: Standardizationmentioning
confidence: 99%
“…A survey of medical students graduating in the United States found that the quality of EOL care education was inadequate. In total, 53% of these students reported learning little or nothing about palliative care from attending non-palliative care classes, and 78% of the students reported learning only a limited amount from residents (10). In addition, Schmit et al (11) reported that residents and fellows considered the EOL care communication skills education they received during medical school and residency to be insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Sabe-se que o tema é abordado de maneira não contínua, não obrigatória e em disciplinas ligadas ao tema da morte, dor, ou relacionado à área de Oncologia, ou seja, não se trata da questão de maneira sistemática como se trata, por exemplo, a anatomia ou a propedêutica 9 . Um estudo recente, que compara a educação médica em CP, observou preocupação com o tema em diversos países, mas com pouca resolutividade quanto a como solucionar este problema 10 . A partir desse estudo, foram traçadas estratégias individualizadas, em poucas das muitas universidades estudadas, com resultados positivos, mas divulgados em escala mínima.…”
Section: Introductionunclassified
“…A partir desse estudo, foram traçadas estratégias individualizadas, em poucas das muitas universidades estudadas, com resultados positivos, mas divulgados em escala mínima. Também foi atestado que a dificuldade em atingir o método ideal de ensino se relaciona à falta de profissionais capacitados para ensinar e assumir a disciplina dentro de serviços médicos por ser este um tema muito novo na medicina em geral 10 .…”
Section: Introductionunclassified